A tale of two LAMS: a report of benign tissue ingrowth resulting in recurrent gastric outlet obstruction - Parekh, Parth J.; Shakhatreh, Mohammad H.; Yeaton, Paul (Endoscopy International Open, 2018)
Background and study aims Endoscopic ultrasound (EUS)-guided gastroenterostomy is a novel, off-label, procedure that has been facilitated by availability of a novel lumen apposing metal stent (LAMS) (Axios, Boston Scientific, Marlbourough Massachusetts, United States). The literature suggests its efficacy to be comparable to surgical gastrojejunostomy. In theory, this procedure overcomes the issues associated with woven enteral stents, which are subject to continuous, straightening, axial forces. We report the adverse event of tissue ingrowth in an Axios stent placed as an EUS-guided gastroduodenostomy, resulting in recurrence of gastric outlet obstruction, treated by a stent-inside-stent technique.